Bacterial translocation in critical illness. (10th February 2017) - Krentz, T.; Allen, S.
Abstract : Bacterial translocation involves the passage of intestinal bacteria to extraintestinal sites and has been shown to increase morbidity and mortality in critical illness. This review outlines the pathophysiology of bacterial translocation, host defence mechanisms, and reviews the evidence for the clinical management of critically ill patients in order to minimise the negative outcomes associated with bacterial translocation.